DEMONSTRATION OF LYSOGENY IN STABLE L FORMS OF PROTEUS MIRABILIS - Taubeneck, Udo (1963)
Taubeneck, Udo (Institut für Mikrobiologie und Experimentelle Therapie, Jena, Germany). Demonstration of lysogeny in stable L forms of Proteus mirabilis. J. Bacteriol. 86:1265–1269. 1963.—Stable L forms of eight different lysogenic Proteus mirabilis strains have proved to be lysogenic. In an additional strain, phage production was induced upon transfer into the stable L form. This demonstrates that the stable L forms, like their parent bacillary types, are capable of forming mature phage. Their phage resistance is not due to an inability to form mature phage but to a loss of phage receptors. In some instances, the transition into the stable L form is associated with altered phage production, usually with increased phage production, in comparison with the parental bacillary type.